SEQUENCING OF MATK GENE FOR TAXONOMIC IDENTIFICATION AND IN VITRO PROPAGATION OF A LOCAL YAM (DIOSCOREA SP.) CULTIVAR GROWN AT MUONG KHUONG, LAO CAI - Bang, Cao Phi; Hong, La Viet (Vietnam Journal of Biotechnology, 2018)
Khoai mo, local name of Yam species belonging to the Dioscoraceae family, is widely grown at Muong Khuong, Lao Cai province because of their important food and pharmaticeutical valuables. This work aimed to sequence the MatK gene obtained from leaves of a local yam grown in Muong Khuong, Lao Cai. The sequencing result showed a partial sequence of the MatK gene which was submitted to GenBank with accession MF494702 provided. The length of this partial sequence is 916 nucleotides. Phylogeny analysis indicated that local yam cultivar grown at Muong Khuong, Lao Cai belonged to Dioscorea alata species. Nodal segments collected from this local yam were used as initial material for in vitro vegetative multiplication. In the shoot formation step, BAP or BAP and NAA complex were used in shoot formation experience. In vitro shooting effect was higher on MS medium supplemented with BAP at 0.3 mg/l of contrentration in compared to other studied BAP concentrations. The presence of NAA at 0.5 mg/l in medium containing BAP promoted a high rate of shoot multiplication. Highest value of shoot production was obtained on MS medium fortified with BAP (1.5 mg/l) and NAA (0.5 mg/l) from nodal segments. In next step, shoots were successfully rooted in vitro. A high number of roots per shoot and highest length of roots were obtained on MS medium containing 0.2 or 0.3 mg/l of NAA. High acclimatization frequencies were obtained when transferred rooted explants to rich soil, yellow clay soil and soil+sand mixture (1:1). Best survival rate (100%) was achieved on rich soil substrate during ex vitro acclimatization process.